School-Based Balanced Nutrition Intervention Program in Preventing Obesity in Adolescents - Kurniati Dwi Utami; Vina Novela; Wijianto (Miracle Journal Get Press, 2026)
Obesity among adolescents has become a significant public health concern, particularly in urban areas undergoing rapid nutritional transition. Purpose: This study aimed to evaluate the effectiveness of a school-based balanced nutrition intervention program in preventing obesity among adolescents by improving knowledge, attitudes, dietary behavior, and physical activity. Method: A quantitative quasi-experimental design with a non-equivalent control group was employed. The study involved 120 students aged 12–18 years in Padang City, divided into intervention and control groups. Data were collected through pre-test and post-test measurements using anthropometric assessment (BMI-for-age z-score), nutrition knowledge questionnaires, attitude and behavior scales, Food Frequency Questionnaire (FFQ), and International Physical Activity Questionnaire (IPAQ). Statistical analyses included descriptive, paired t-test, and independent t-test. Results: The intervention group showed a significant reduction in BMI z-score (Δ = −0.53; p < 0.001) and obesity prevalence (35.0% to 18.4%), along with significant improvements in nutrition knowledge (Δ = +16.2), attitudes (Δ = +13.6), dietary behavior (Δ = +14.5), and physical activity (Δ = +400 MET) (p < 0.001). In contrast, the control group showed no significant changes (p > 0.05). Implications: The findings highlight the effectiveness of integrated school-based interventions combining nutrition education, environmental modification, and physical activity promotion in addressing adolescent obesity. Conclusion: The balanced nutrition intervention program is effective in improving health behavior and reducing obesity risk among adolescents, supporting its implementation as a sustainable school health strategy.